MENYINGKAP TEORI SEKSUALITAS PSIKOANALISA SIGMUND FREUD DAN USAHA PENERAPANNYA DALAM PENDIDIKAN SEKSUALITAS - Kwirinus, Dismas (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
The focus of this research is on psychoanalytic sexuality and education. The researcher intends to first look at Freud's theory of sexuality and try to find ways to apply it. This study uses a descriptive qualitative method that produces data in the form of words and in writing or verbally from the people and observed behavior. This study aims to describe, analyze, the stages, meanings and provide responses to the psychoanalytic theory of sexuality and make it happen through efforts to apply it in sexuality education. Researchers also want to contribute ideas for sexuality education which is currently considered necessary. So that with this in mind can help parents and educators in carrying out sexuality education in infants, children and adolescents. Sexuality education feels so important today. This is considering the negative impact of technological advances that can bring abuse of sexual nature. With the existence of sexuality education in children, sexual abuse that is not in accordance with the norms of society, religion, law and morals can at least be reduced and controlled.